Association between intimate partner psychological violence and psychological distress among nurses: The role of personality traits and social support - Huang, Wentao; Zhang, Fan; Sun, Xibin; Yu, Qing; Huang, Jingxin; Su, Yunhui; Lan, Yutao (Frontiers in Psychology, 2023)
Aim This study proposes investigating the risk and protective factors of intimate partner psychological violence and psychological distress to promote better psychological well-being for nurses and patients' health outcomes. Design A cross-sectional study. Method This cross-sectional study was carried out chiefly in the Guangdong, Hunan, and Shaanxi Province, in the Chinese economic areas east, central, and west. This study was conducted in October 2021, using convenience sampling. A total of 843 nurses were eligible for final analysis. Single-factor linear regression models were used to identify potential factors associated with an intimate partner psychological violence and psychological distress. In addition, the structural equation model was used to explore the role of personality traits and social support in the association between intimate partner psychological violence and psychological distress. Results The predictors for the score of IP psychological violence among nurses were participants’ married status, contact frequency with a partner, perceived past year psychological and physical violence experience, partner’s alcohol consumption, partners’ personality traits and social support. Moreover, participants’ alcohol consumption, past year experience of intimate partner psychological violence, the score of psychological violence, personality traits, social support, and the partner’s personality traits were associated factors affecting nurses' psychological distress. In the structural model, partner’s personality trait had a direct pathway to psychological violence and social support. The results demonstrated that psychological violence significantly increased psychological distress. Conclusion Personality traits and social support are essential factors influencing the relationship between intimate partner psychological violence and psychological distress. Impact The finding of this study emphasizes the possibility and importance of identification and intervention for reducing intimate partner psychological violence based on personality traits and social support.